Performance evaluation of submerged membrane bioreactor for the removal of microalgae from the source water of a water treatment plant - Thiruchchelvam, Thinojah; Kalahara, Walimuni Dissanayakage Lakshitha Manula; Abeykoon, Yatikindage Malith Dilshan; Balachandran, Ketheesan (Elsevier, 2023)
Freshwater algal blooms negatively impact the operations of water treatment plants when they are present in the source water. In the present study, an application of a low-cost submerged microfiltration membrane bioreactor for the removal of microalgae from a source water reservoir of a water treatment plant was evaluated. The experiments were conducted in different phases to systematically evaluate how different fouling control methods such as air scouring and water backwashing in combination with vibration technique can enhance the flux and removal efficiency of microalgae in a submerged flat sheet microfiltration membrane bioreactor. Combining backwashing with air scouring (Phase 3) positively enhanced the flux by reducing the TMP, but it did not improve the permeate quality in terms of microalgae and turbidity removal. The results of Phase 4 studies confirmed that vibration had a profound effect on microalgae removal compared to backwashing technique while reducing the TMP from 105 to 103 kPa. The average turbidity removal was increased from 76.75% to 82% when vibration is applied. Combining all fouling control methods such as air scouring, backwashing and vibration methods did not appear to be effective for the removal of microalgae and turbidity (Phase 5). In order to signify the energy input on membrane fouling control, flux in each phase was assessed with respect to total power input. In overall, air scouring at a rate of 7 L/min with 50 Hz of vibration appeared to be an optimum condition in controlling fouling without any frequent backwashing.
Keywords: Air scouring; Algae fouling; Backwashing; Flat sheet membrane; Vibration; Energy consumption